2000
DOI: 10.1002/1099-1158(200010)5:4<309::aid-ijfe136>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Political instability and economic vulnerability

Abstract: This paper analyzes and tests the influence of political instability on economic vulnerability in the context of the 1994 and 1997 crisis episodes. It constructs four political variables that aim at quantifying political instability. The paper finds that, for countries with weak economic fundamentals and low reserves, political instability has a strong impact on economic vulnerability. The estimation results suggest that including political variables in economic models does improve their power to explain and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 21 publications
(22 reference statements)
0
23
0
Order By: Relevance
“…Economic, financial, governance, political, and social reforms are being pursued worldwide (Bussiere & Mulder, 2000;Gupta, Baldacci, Clements, & Tiongson, 2005;Swamy & Dharani, 2018). Recent corporate scandals have directed more attention to CG and EP mechanisms (Hasan, Kobeissi, & Song, 2014;Ullah, Ahmad, Akbar, & Kodwani, 2018a), especially on the importance of board of directors in terms of their roles, effectiveness, composition, and diversity (Carter, D'Souza, Simkins, & Simpson, 2010;Carter, Simkins, & Simpson, 2003;Yamori, Harimaya, & Tomimura, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Economic, financial, governance, political, and social reforms are being pursued worldwide (Bussiere & Mulder, 2000;Gupta, Baldacci, Clements, & Tiongson, 2005;Swamy & Dharani, 2018). Recent corporate scandals have directed more attention to CG and EP mechanisms (Hasan, Kobeissi, & Song, 2014;Ullah, Ahmad, Akbar, & Kodwani, 2018a), especially on the importance of board of directors in terms of their roles, effectiveness, composition, and diversity (Carter, D'Souza, Simkins, & Simpson, 2010;Carter, Simkins, & Simpson, 2003;Yamori, Harimaya, & Tomimura, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this finding, Stein and Streb (1998) and Bussière and Mulder (2000) recall several instances in which governments chose not to address real issues before an election so as to keep inflation and the exchange rate under control. However, those authors' observations remain anecdotal.…”
Section: U Umentioning
confidence: 53%
“…For instance, Edwards (1994) found that in Latin American presidential democracies 77 per cent of the devaluations took place within the first 18 months of the government being in office. His finding is corroborated by Klein and Marion (1997), Eichengreen et al (1995) and Bussière and Mulder (2000) who observed that the probability of a devaluation significantly increases in post-election periods. Furthermore, Eichengreen et al (1995) also provide some evidence that revaluations tend to follow government defeat.…”
Section: Imentioning
confidence: 63%
“…It has been well documented that weak political institutions contribute significantly to the likelihood of currency crises (Edwards 1996;Bernhard and Leblang 1999;Bussiere and Mulder 2000;Frieden, Ghezzi, and Stein 2001;Poirson 2001;Block 2002;Meon and Rizzo 2002;Alesina and Wagner 2003;Calvo and Mishkin 2003;Shimpalee and Breuer 2006). Here we go further to test the hypotheses developed by Willett (2007) that political instability and weak governments more generally are an important part of the explanation for the crisis proneness of adjustable-peg exchange rate regimes.…”
Section: Literature Review and Explanation Of Hypothesesmentioning
confidence: 82%